The prevalence of careless response behaviour and its consequences on data quality in self-report questionnaires on student learning - Chauliac, Margot; Willems, Jonas; Gijbels, David; Donche, Vincent (Frontiers in Education, 2023)
Self-report questionnaires are widely used in high schools and universities to gain insights into students' learning strategies and enhance the quality of their education. However, it is important to acknowledge the possibility of respondents being inattentive when completing these questionnaires. While reliability analyses are typically performed at the group level, when providing individual feedback, it is crucial that each respondent's results are reliable. This study aimed to evaluate the prevalence of careless response behaviour in a questionnaire concerning student learning. For this purpose, we analysed data collected from over 12,000 students in their final two years of secondary education, aged approximately 17 years on average. By employing five complementary detection techniques, our findings reveal that careless responding is a significantly prevalent issue. Furthermore, we assessed the reliability of the measurement scales and concluded that, although carelessness is present, its impact at the group level remains minimal. These findings emphasise the importance of individually screening respondents for careless responses, underscoring the need for meticulous consideration of individual-level analysis.